2014
DOI: 10.1016/j.ymgme.2014.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of low-phenylalanine protein sources on brain neurotransmitters and behavior in C57Bl/6-Pahenu2 mice

Abstract: Phenylketonuria (PKU) is an inborn error of metabolism caused by a deficiency of the enzyme phenylalanine hydroxylase, which metabolizes phenylalanine (phe) to tyrosine. A low-phe diet plus amino acid (AA) formula is necessary to prevent cognitive impairment; glycomacropeptide (GMP) contains minimal phe and provides a palatable alternative to the AA formula. Our objective was to assess neurotransmitter concentrations in brain and the behavioral phenotype of PKU mice (Pahenu2 on the C57Bl/6 background) and how … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 64 publications
2
12
1
Order By: Relevance
“…Both strains showed a vast increase in Phe levels and disrupted serotonin and norepinephrine levels in the brain (for norepinephrine a trend was observed for BTBR statistically) which is in accordance with previous studies (Andolina et al, 2011; Pascucci et al, 2013; Sawin et al, 2014; van Vliet et al, 2015). How these PKU-related changes can result in a different functional outcome is not clear.…”
Section: Discussionsupporting
confidence: 91%
“…Both strains showed a vast increase in Phe levels and disrupted serotonin and norepinephrine levels in the brain (for norepinephrine a trend was observed for BTBR statistically) which is in accordance with previous studies (Andolina et al, 2011; Pascucci et al, 2013; Sawin et al, 2014; van Vliet et al, 2015). How these PKU-related changes can result in a different functional outcome is not clear.…”
Section: Discussionsupporting
confidence: 91%
“…As shown before (Ney et al 2008;Solverson et al 2012;Sawin et al 2014), Phe levels in plasma and brain of SedPKU mice were higher in comparison to respective levels in SedWT group (p < 0.001). Exercise did not modify Phe levels when comparing each Exe group to its Sed control (Fig.…”
Section: Resultssupporting
confidence: 65%
“…Recently, it has also been demonstrated that these patients are more susceptible to neurological symptoms caused by cerebral dopamine deficiency, such as Parkinsonism [2]. Indeed, several studies have shown that high Phe concentrations is associated with decreased serotonin, dopamine, and norepinephrine levels in human and murine PKU [48][49][50][51][52]. The decrease of these neurotransmitters levels could be related to the effect of high Phe concentration on amino acids transport through the blood-brain barrier (BBB) (such as Tyr and tryptophan -Trp) or on enzymes involved in neurotransmitters synthesis [48].…”
Section: Neurotransmitters Metabolismmentioning
confidence: 99%
“…The decrease of these neurotransmitters levels could be related to the effect of high Phe concentration on amino acids transport through the blood-brain barrier (BBB) (such as Tyr and tryptophan -Trp) or on enzymes involved in neurotransmitters synthesis [48]. It is important to stress out that large neutral amino acid (LNNA) transporter has high affinity for Phe, which competes with other amino acids to cross BBB [53], consequently reducing the amount of Trp and Tyr available for neurotransmitter synthesis [52,54,55]. Phe is also a competitive inhibitor of Tyr hydroxylase (EC # 1.14.16.2) and Trp hydroxylase (EC # 1.14.16.4), important enzymes for the brain synthesis of the neurotransmitters dopamine and serotonin, respectively [56][57][58][59][60].…”
Section: Neurotransmitters Metabolismmentioning
confidence: 99%